Use of antibiotics among end-of-life hospitalized patients with advanced directives: Status examination and association with infectious disease consultation and physician burnout. (28th August 2019) - Fedorowsky, Rina; Bachner, Yaacov G.; Borer, Abraham; Ciobotaro, Pnina; Kushnir, Talma
Abstract: Background: Overuse of antibiotics in end-of-life patients with advanced directives increases bacterial resistance and causes morbidity and mortality. Consultations with infectious disease (ID) physicians and burnout, which can affect antibiotic days of therapy (DOT) prescribed by physicians, have not been examined so far. Objectives: To assess antibiotic use by physicians in end-of-life (EOL) patients with advanced directives and to investigate the association between ID consultations, physician burnout, and antibiotic DOT in those patients. Design: A descriptive correlational study. Setting: Acute-care and post–acute-care hospitals. Participants: The study included 213 physicians and 932 their hospitalized patients in the last 2 weeks of life Methods: We distributed questionnaires and analyzed the data collected regarding ID consultation, EOL antibiotics prescription with and without an advanced directive, and physician burnout to 278 physicians, and 213 were completed (response rate 76%). Results: Of the 932 deaths, 435 of 664 (>50%) were EOL patients with advanced directives. Of these patients, 74% received antibiotics, 29.9% had bacterial resistance cultures, and antibiotics were discontinued in only 5%. Half of the physicians lacked knowledge concerning antibiotics use issues and had significantly fewer consultations with ID physicians in EOL patients with advanced directives (mean rate, 0.27) than those without advanced directives (mean rate, 0.47). ID physicians reported significantly higher emotional exhaustion levels (mean rate, 29) than other medical specialties (mean rate, 19.2). Antibiotic DOT was significantly higher when patients had ID consultations (mean rate, 21.6) than in patients who did not (mean rate, 16.2). In post–acute-care hospitals and/or geriatric wards, antibiotic DOT was significantly higher than in other types of hospitals and/or wards. Depersonalization level was negatively related to antibiotic DOT ( P < .05). Conclusions: Antibiotics are overused in EOL patients with advanced directives. ID physician burnout and impact of ID consultation should be further assessed.